APPLICATION OF FRACTAL CONCEPT IN MATERIAL BATIK DEVELOPMENT BASED ON WOLFRAMS MATHEMATICA - Marom, Saiful (UIN Sumatera Utara, 2017)
The geometry concept has been developed rapidly, one of them is about fractal geometry. In fractal geometry concept, it has been discussed about shapes which have fractal dimension characteristics. In fractal geometry concept, it would resulted in a look like irregular shape. But if it had been observed closer, it would found a regular shape. Self-similarity is a characteristic in fractal geometry when diferent magnifications was found. In fractal concept, a pattern would be obtained from a function itteration by an infinite repetition. One of fractal geometry application is in batik design fabrications. This idea based on equality dimension, that is both of them is in fractal dimension. In fractal geometry, it will result in a specific design by itterated function using Wolframs a program.